Extended Stability of Sodium Phosphate Solutions in Polyvinyl Chloride Bags - Perks, William (Can J Hosp Pharm, 2017)
BACKGROUND: Sodium phosphate injection is used to treat moderate to severe hypophosphatemia. There have been no published reports documenting the physical compatibility or chemical stability of sodium phosphate injection in IV solutions. OBJECTIVE: To evaluate the physical compatibility and chemical stability of 30 and 150 mmol/L solutions of phosphate, prepared from sodium phosphate injection, in 5% dextrose in water (D5W) and in 0.9% sodium chloride (normal saline [NS]) and stored in polyvinyl chloride (PVC) bags at 23°C or 4°C over 63 days. METHODS: On study day 0, solutions of phosphate 30 and 150 mmol/L in D5W or NS were prepared in PVC bags and stored at 4°C and 23°C. On prespecified days during the 63-day study period, the concentrations of sodium and phosphate were determined, and admixture weight was checked to assess moisture loss during storage without a plastic overwrap. Chemical stability was calculated from the intersection of the lower 95% confidence limit of the degradation rate and the lower limit of acceptability (90%) for concentration remaining. RESULTS: The analytical methods for both sodium and phosphate were found to be precise (coefficient of variation averaging less than 1% for pre-study validation samples). Both sodium and phosphate retained more than 94% of the initial concentration over the 63-day study period. With 95% confidence, the time to achieve 90% of the initial concentration of both sodium and phosphate approached or exceeded the 63-day study period, regardless of temperature, concentration, or base solution. CONCLUSIONS: Sodium phosphate solutions at a phosphate concentration of 30 or 150 mmol/L in either NS or D5W retained more than 94% of the initial concentration of both sodium and phosphate over 63 days when stored at 23°C or 4°C. In compliance with United States Pharmacopeia General Chapter <797> recommendations, a beyond-use date of 14 days (with refrigeration) or 48 h (room temperature) may be applied. Extending the beyond-use date beyond these limits may be considered, if a validated sterility test is performed.